Consciousness for fair consumption: conceptualization, scale development and empirical validation. (23rd May 2013) - Balderjahn, Ingo; Peyer, Mathias; Paulssen, Marcel
Abstract: Sustainable consumption means that consumers act in an environmentally and socially responsible manner. Compared with the vast amount of studies concerning environmentally conscious consumer behaviour, relatively little is known about socially conscious consumption. The present paper focuses on fair consumption as an important aspect of social consumption. In our study, consciousness for fair consumption (CFC) is defined as a latent disposition of consumers to prefer products that are produced and traded in compliance with fair labour and business practices. A scale to measure CFC was conceptualized and tested in three independent empirical studies. Two studies were conducted at European universities (2010 and 2012) and used 352 and 362 undergraduate business students respectively. The third study, conducted in 2011, used 141 employees at a European university. The results confirmed the reliability and validity of the new CFC scale across samples. While being moderately related to other aspects of sustainable consumption such as ecological concern and moral reasoning, CFC was significantly distinct from those concepts. Most importantly, it was established that the CFC, as measured by the new CFC scale, is a strong determinant of consumption of fair trade products that has been neglected in existing research.